2019
DOI: 10.1038/s41467-019-10735-7
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 fusion to dominant-negative 53BP1 enhances HDR and inhibits NHEJ specifically at Cas9 target sites

Abstract: Precise genome editing/correction of DNA double-strand breaks (DSBs) induced by CRISPR-Cas9 by homology-dependent repair (HDR) is limited by the competing error-prone non-homologous end-joining (NHEJ) DNA repair pathway. Here, we define a safer and efficient system that promotes HDR-based precise genome editing, while reducing NHEJ locally, only at CRISPR-Cas9-induced DSBs. We fused a dominant-negative mutant of 53BP1, DN1S, to Cas9 nucleases, and the resulting Cas9-DN1S fusion proteins significantly block NHE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
124
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 51 publications
3
124
1
Order By: Relevance
“…CRISPR/Cas-based approaches for targeted genome modification have revolutionized modern biology and hold great promise for therapeutic interventions for debilitating genetic disorders. In particular, engineered enzymes have given the gene editing field an everexpanding set of tools with increased fidelity (Kleinstiver et al, 2016;Slaymaker et al, 2016), altered target specificities (Chatterjee et al, 2018;Hu et al, 2018;Nishimasu et al, 2018;Walton et al, 2020), the ability to directly introduce specific changes to a target genome (Gaudelli et al, 2017;Komor et al, 2016;Nishida et al, 2016), or improved genome modification capabilities (Aida et al, 2015;Charpentier et al, 2018;Gu et al, 2018;Jayavaradhan et al, 2019;Nakade et al, 2018;Rees et al, 2019). However, these options continue to suffer from low efficiencies, high indel rates, a narrow scope of editing outcomes, and/or a reliance upon restricted sets of suitable protospacer adjacent motifs (PAMs) in close proximity to the target site.…”
Section: Introductionmentioning
confidence: 99%
“…CRISPR/Cas-based approaches for targeted genome modification have revolutionized modern biology and hold great promise for therapeutic interventions for debilitating genetic disorders. In particular, engineered enzymes have given the gene editing field an everexpanding set of tools with increased fidelity (Kleinstiver et al, 2016;Slaymaker et al, 2016), altered target specificities (Chatterjee et al, 2018;Hu et al, 2018;Nishimasu et al, 2018;Walton et al, 2020), the ability to directly introduce specific changes to a target genome (Gaudelli et al, 2017;Komor et al, 2016;Nishida et al, 2016), or improved genome modification capabilities (Aida et al, 2015;Charpentier et al, 2018;Gu et al, 2018;Jayavaradhan et al, 2019;Nakade et al, 2018;Rees et al, 2019). However, these options continue to suffer from low efficiencies, high indel rates, a narrow scope of editing outcomes, and/or a reliance upon restricted sets of suitable protospacer adjacent motifs (PAMs) in close proximity to the target site.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we demonstrated that this method can be used in combination with the CRISPR/Cas9 method to improve the efficiency of gene targeting. To enhance HDR, key factors involved in NHEJ, such as DNA-PKcs, Ku70, and DNA ligase IV, have been inhibited by widely used methods, such as shRNA-treatment, proteolytic degradation, or treatment with small molecules [38][39][40] . In HDR, the 5′-end of a DSB is resected to create ssDNA carrying a 3′ overhang.…”
Section: Discussionmentioning
confidence: 99%
“…However, HDR efficiency is limited by the presence of a competing repair pathway that is far more efficient, NHEJ. To enhance the frequency of HDR, global inhibition of key NHEJ factors has been the most widely studied strategy [38][39][40] . Although these approaches are effective in increasing the frequency of HDR, further improvements are required to achieve more practical HDR-based genome engineering.…”
Section: Direct Gene Targeting In Fertilized Mouse Eggs By Pronuclearmentioning
confidence: 99%
“…For our study, repair molecules were chosen based on previous reporters highlighting their impact on DNA repair outcomes 28,32,33,34,23,27 . We found that N-terminal fusion of Rad52 and eRad18 improved the knockin precision of Cas9.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have independently demonstrated that modulation of DNA repair pathways is an effective way to improve knockin efficacy and precision 26,13,23,27,28 . To further improve on the in vivo results using CtIP-fused Cas9, we returned to the in vitro BFP-to-GFP conversion assay with an HMEJ donor, and evaluated the impact of five DNA repair proteins (dn53BP1, TIP60, RNF169, Rad52, eRad18) on editing efficiency and precision when fused N-terminally to Cas9 or Cas9-CtIP (Fig.…”
Section: Compound Cas9-ctip Fusions With Erad18 and Rad52 Improve Edimentioning
confidence: 99%